Mini-hearts for disease modeling and drug testing – process optimization versus biological functionality - Hecking, Jana; Cano-Jorge, Mariel; Passier, Robert; Rivera-Arbeláez, José Manuel (Frontiers in Bioengineering and Biotechnology, 2026)
Traditional two-dimensional cell cultures and in vivo animal studies fail to fully recapitulate human cardiac physiology, highlighting the urgent need for more relevant human-based models. Engineered three-dimensional cardiac systems - including organoids, engineered heart tissues, and heart-on-chip platforms offer promising alternatives, providing structural and functional insights into cardiac biology. However, a critical limitation of these models is their inability to perform fluid pumping and relaxation, which together define fundamental heart function. Engineered cardiac chambers have emerged to address this gap, enabling physiologically relevant pressure-volume measurements and capturing both contractile and diastolic dynamics that mimic aspects of native cardiac hemodynamics. This mini-review examines the current state of engineered cardiac chambers and highlights their main design features. We discuss their applications in disease modeling and drug testing, and outline key factors influencing the optimization of these models, including balancing biological fidelity with process efficiency through modular design principles. Overall, engineered cardiac chambers represent a unique, powerful platform to improve mechanistic understanding of cardiac disease, offering significant potential to advance cardiovascular research and therapeutic development.